دلالة الألفاظ باعتبار وضوحها بين بنائها اللغوية والقرائن المقاصدية _دراسة تحليلية تطبيقية_ البحث مستل من أطرحة دكتوراه - الدّين, بختيار نجم الدّين شمس; غفار, جلال جمال (Sulaimani Journal for Humanities, 2023)
This research deals with an important topic, it talks about the issue of linking texts with their purposes and foresights, and verily this is a very sensitive issue, because there are some texts, which a particular ruling is taken from their apparent meaning, and from their deep meaning purpose another ruling is meant. There is no doubt that understanding the basic meaning of each text is faster to get in mind, when there is no prior presumption. However, in many cases this shallow meaning is not the original purpose of the discourse, and not what the context came for. Therefore, diverting the text and discourse from its basic meaning to a deeper purpose is better. What is really helping us in that the presence of a clear intentional presumption from this basic apparent meaning which converts it to a deep purpose that the context really meant. The lack of understanding of these deep intentions may lead to hardship, and the Islamic Ummah (Nation) will fall into many mistakes and deviations, also disagreement in many issues